PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DALAM RANGKA PELAKSANAAN REDISTRIBUSI TANAH PADA KANTOR PERTANAHAN KABUPATEN LAMPUNG TIMUR - Yuliansyah, Iwan; Suharto, Suharto; Dacholfany, Muhammad Ihsan (SIMPLEX: Journal of Economic Management, 2024)
This study aims to determine empirically: 1) Organizational culture influences employee performance in the context of implementing land redistribution at the East Lampung Regency Land Office. 2). Work Motivation affects Employee Performance in the context of Implementing Land Redistribution in the Land Office of East Lampung Regency. 3). Organizational Culture and Work Motivation affect Employee Performance in the context of Implementing Land Redistribution in the Land Office of East Lampung Regency. This research was conducted at the Land Office of East Lampung Regency with a population of 40 respondents. Data analysis used validity, reliability, product moment correlation analysis and regression analysis. The results showed that 1) Organizational Culture has an effect on Employee Performance in the context of Implementing Land Redistribution in the Land Office of East Lampung Regency. 2). Work Motivation affects Employee Performance in the context of Implementing Land Redistribution in the Land Office of East Lampung Regency. 3). Organizational Culture and Work Motivation affect Employee Performance in the context of Implementing Land Redistribution in the Land Office of East Lampung Regency. The magnitude of the influence of Organizational Culture and Work Motivation on Employee Performance in the context of Implementing Land Redistribution at the Land Office of East Lampung Regency is 25.6%.